Surveillance of Regional Public Service Authorities: Analysis of Regulation and Its Impact on Public Service Efficiency - Arifin, Firdaus (Faculty of Law, Mulawarman University, 2024)
The oversight of the Regional General Service Agency (BLUD) in Indonesia has faced various challenges in terms of effectiveness and implementation, which may hinder the achievement of the objectives of transparency and accountability in the management of public finances. The study aims to evaluate the effectiveness of BLUD surveillance by identifying factors that affect regulatory compliance and BLUD performance in the provision of public services. Using a mixed methodological approach, the study combines normative and empirical analysis, as well as using comparative and socio-legal methods to dig up qualitative and quantitative data from various regions in Indonesia. The results of the study show that although the regulatory framework has been adequate, the implementation of surveillance still faces obstacles such as limited resources and less effective inter-agency coordination, which ends with variations in BLUD compliance and performance. The findings reaffirm the importance of strengthening surveillance capacity as well as revising policies that are adaptive to local conditions. Implications of this study include recommendations for enhanced, more integrated, technology-based supervision to support better public finance governance.